PENINGKATAN SELF ESTEEM SISWA KORBAN BULLYING MELALUI TEKNIK ASSERTIVE TRAINING - Mujiyati, Mujiyati (JURNAL FOKUS KONSELING, 2015)
This study is based on studentsâ problem who undergone the decreasing of self-esteem due to bullying that students receive in their environment. The long-term goal which going to be achieved is related to self esteem problem of students bullying victims that is capable to solve problem by using effective and tested product through counseling with assertive training technique. This study used research and development method. The steps are: (1) preliminary research; (2) designing model; (3) developing model; (4) testing model restrictively; (5) analysing model; (6) revising model; (7) testing model widely; (8) dissemination of model; and (9) recommending tested model. The result of study showed that the model of counseling through assertive training was empirically proven effective to improve self esteem of students bullying victims.Keywords: Self Esteem, Bullying, Assertive Training